Analytical Solution for Rayleigh Wave-Induced Dynamic Response of Shallow Grouted Tunnels in Saturated Soil - Haifeng Huang; Mingyu Chang; Pengfa Zhou; Yang Luo; Chao Wang; Yusheng Shen; Kaixiang Fan; Bo Gao (Buildings)
The dynamic interaction between shallow cylindrical tunnels with grouting reinforcement zones and saturated poroelastic medium under Rayleigh surface wave excitation is investigated. Employing the wave function expansion method within the framework of Biot theory, the analytical solution is derived in the frequency domain. A comprehensive parametric analysis evaluates the influence of critical parameters—including input frequency, the stiffness and thickness ratios between the tunnel lining and grouting zone, as well as tunnel burial depth—on the dynamic behavior of the composite structure. The spatial distributions of dynamic stress concentration factors and pore pressure concentration factors obtained in this study may offer critical insights for optimizing seismic resilience design in tunnel engineering.